An enterpreneural characterisation of the supply chain system of automobile battery in Ibadan southwest Nigeria. (2011)
Problems such as the importation of substandard auto batteries are some of the challenges confronting the supply of the product in Nigeria. In this work some aspects of the supply chain system of the automobile batteries have been studied in Oyo state, Nigeria. The automobile battery supply chain system has been segmented into three: suppliers, users and the repairers for analysis. Using direct observation, questionnaires relevant data on each of these three segments were collected and analysed based on typical 12 Volts automobile battery. Data obtained from the vehicle licensing office was used to illustrate and analyse the entrepreneurship opportunities of the automobile battery market in Nigeria. The study reveals a huge market in the supply system of the auto battery in Nigeria. Also provide a template applicable to the analysis of other engineering products.